EFEKTIFITAS PEMANFAATAN GOOGLE FORMULIR SEBAGAI SISTEM PENGUMPULAN DOKUMEN PENYALURAN TUNJANGAN PROFESI GURU MADRASAH DI KANTOR KEMENTERIAN AGAMA KABUPATEN CILACAP - Sitti Sururiyah (QALAM: JURNAL PENDIDIKAN ISLAM, 2020)
This article is intended to get an overview of the process of collecting the distribution of documents for the professional madrasah teacher . the Ministry of Religion Cilacap Regency and to find out the effectiveness of the service applying the document collection policy using Google forms media. The research method and analysis uses a qualitative descriptive approach. The results showed that the process of collecting documents the professional madrasah teacher could be seen from 3 aspects. First, responsiveness . the Ministry of Religion Cilacap Regency as a service provider and the professional madrasah teacher as service users showed a positive response. The second, development,  is the innovation that has been carried out by  the Ministry of Religion Cilacap Regency from being initially based on manual to being based online. Third, the adequacy in which all stages of the filing program stage have been running quite effectively and smoothly. From the results of the discussion of these three aspects, it was concluded that the service system for collecting documents on the distribution of the professional madrasah teacher at the Ministry of Religion Cilacap Regency was effective.